2022
DOI: 10.1364/optica.441682
|View full text |Cite
|
Sign up to set email alerts
|

Chemical element mapping by x-ray computational ghost fluorescence

Abstract: Chemical element mapping is an imaging tool that provides essential information on composite materials and it is crucial for a broad range of fields ranging from fundamental science to numerous applications. Methods that exploit x-ray fluorescence are very advantageous and are widely used, but require focusing of the input beam and raster scanning of the sample. Thus the methods are slow and exhibit limited resolution due to focusing challenges. We demonstrate a new focusing free x-ray fluorescence method base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This agrees with the width of the measured autocorrelation function Extended Data Fig. 4 and indicates that further improvement of the spatial resolution is feasible by a simple reduction of the speckle size 34 . As shown in Extended Data Fig.…”
Section: Extended Data Experiments At Lower Photon Energysupporting
confidence: 87%
See 2 more Smart Citations
“…This agrees with the width of the measured autocorrelation function Extended Data Fig. 4 and indicates that further improvement of the spatial resolution is feasible by a simple reduction of the speckle size 34 . As shown in Extended Data Fig.…”
Section: Extended Data Experiments At Lower Photon Energysupporting
confidence: 87%
“…This is because in CGI the spatial information is derived from the spatially modulated beam, which interacts with the object, rather than from the detector pixels. While X-ray CGI has been demonstrated with transmitted [30][31][32][33] , fluorescent 34 , and refracted radiation 35 , we apply it to incoherent scattered radiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns are used to form a reconstructed image through correlation calculation. Owing to its wide range of light sources and strong anti-interference ability, GI has attracted significant attention in several related fields such as X-ray imaging 1 , 2 , terahertz imaging 3 , acoustic imaging 4 , three-dimensional imaging 5 , 6 , fluorescence imaging 1 , optical encryption 7 , 8 , and underwater imaging 9 15 . The application scenarios and influencing factors of GI are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the imaging qualities of orthogonal and random speckle patterns in air 13 has shown that orthogonal speckle patterns are more suitable for low-sampling CGI. Owing to its wide range of light sources and strong antiinterference ability, GI has attracted significant attention in several related fields such as X-ray imaging 14,15 , terahertz imaging 16 , acoustic imaging 17 , three-dimensional imaging 18,19 , fluorescence imaging 14 , optical encryption 20,21 , and underwater imaging [22][23][24][25][26][27] . Application scenarios and influencing factors of GI are shown in Fig.…”
mentioning
confidence: 99%